Effect of material and time of refilling on the growth, plant population and grain yield of maize under no-tillage system - Akowuah, Patrick (2011)
A Thesis submitted to the Department of Crop and Soil Sciences, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana, in partial fulfillment of the requirement to the degree of MASTER OF SCIENCE (Msc.).